Dampak Tumpang Tindih Bahasa Ibu Dalam Perkembangan Bahasa Anak - Ajeng Priendarning Tyas (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to collaborate theory with practice that occurs in the field, also knowing that the use of mother tongue in early childhood is very important. The research method used is descriptive qualitative with literature study in the form of photos, notes, and books. The results of this study are the occurrence of overlap in language development in children is very influential and has an impact on self and communication. The stimulation given cannot be instant but is carried out continuously. Because the child's grasping power will adjust how the language is given so that what kind of reinforcement will be generated. The use of mother tongue that is not optimal will cause language overlap. The occurrence of overlaps can result in difficulties in developing children's language development in everyday life; such as to communicate and interact with other people and the environment, impaired concentration, and unstable behavior. Keywords: Literature study, Mother languange, Language development References Arikunto. (2010). Prosedur Penelitian : Suatu Pendekatan Praktek. Jakarta : Rineka Cipta. Azizah, N., & Dewi, A. C. (2021). Analisis Perkembangan Bahasa Semantik Dan Sintaksis Anak Dalam Kegiatan Belajar Dari Rumah. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 6(2), 139–146. Brown, R. (1964). Three Process in the Child’s Aquisition of Syntax. Harvard Eduvational Review. Chomsky. (1962). Explanatory Models in Linguistics. Stanford : Stanford University Press. Chomsky. (1969). The Acquisition of Syntax in Children from 5-10. Cambridge, MA : MIT Press. Humaeroh, H. (2016). Pembelajaran Bahasa Pada Anak Yang Mengalami Keterlambatan Berbicara Untuk Meningkatkan Kemampuan Berkomunikasi. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 126–138. Imroatun, I. (2018). Alternatif Media Pengembangan Literasi Baca Tulis Berbahasa Nasional bagi Siswa Raudlatul Athfal AH-. Al Hikmah Proceedings on Islamic Early Childhood Education, 1(April), 103–112. Imroatun, I., Nirmala, I., Juhri, J., & Muqdamien, B. (2020). Kajian Literatur Pengasuhan Anak Usia Dini Dalam Islam. As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 5(1), 57–66. Jonathan, Sarwono. (2006). Metode Penelitian Kuantitatif dan Kualitatif. Yogyakarta : Graha Ilmu. Kuhltau, C. C. (2002). Teaching The Library Research. USA : Scarecrow Press Inc. Ma’isyah, N. (2018). Pengembangan Modul Membaca Lancar Pokok Bahasan Lingkungan Yang Bernuansa Kontekstual. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(2), 137–146. Montessori. (1936a). The Child in The Family (N.R Cirillo. Terj). Chicago : Henry Regnery Co., 1970. Montessori. (1936b). The Secret of Childhood (M.J Costelloe, Terj). New York : Ballatine Books, 1966. Nazir. (1988). Metode Penelitian. Jakarta : Ghalia Indonesia. Nurhayati, R. (2019). Membangun Budaya Literasi Anak Usia Dini dalam Keluarga. Nuansa Akademik: Jurnal Pembangunan Masyarakat, 4(1), 79–88. https://doi.org/10.47200/JNAJPM.V4I1.918 Sachs, J.S. (1976). Development of Speech. New York : Academic Press. Suryana, D. (2016). Pendidikan Anak Usia Dini (Stimulasi & Aspek Perkembangan Anak). Kencana.